Variation in the Accumulation of Phytochemicals and Their Bioactive Properties among the Aerial Parts of Cauliflower - Natalia Drabińska; Maja Jeż; Mariana Nogueira (MDPI AG, 2021)
Vegetables from the Brassicaceae family are excellent sources of bioactive phytochemicals and may reduce the risk of chronic diseases. Variation of phytochemicals in the edible part of cauliflower is known. However, information about the distribution of bioactive and nutritive compounds as well as antioxidant activity among aerial organs of cauliflower is unavailable. Therefore, this study aimed to evaluate the distribution of glucosinolates (GLS), phenolics, flavonoids, chlorophylls, nutritive compounds and antioxidant capacity between the aerial parts of the common variety of cauliflower and to evaluate whether these changes contribute to the differences in the antioxidant capacity between the plant organs. Our study showed that all the aerial organs of cauliflower are a rich source of health-promoting bioactive compounds, including GLS, phenolics and flavonoids, exhibiting antioxidant capacity. The highest contents of phytochemicals and the highest antioxidant capacity were found in leaves. Cauliflower organs were also found to be rich in nutritive compounds, including minerals, proteins and amino acids. Our study showed that the non-edible organs, such as stems and leaves, being neglected parts of cauliflower, if not consumed as the main ingredient, can be used as additives for developing new, functional foodstuff.